Effect of Exhaust Gas Recirculation on CO Emissions from A Turbocharged Diesel Engine (University of Khartoum Engineering Journal, 2022)
In this paper an experimental investigation was conducted to study the effect of using different ratios ofExhaust Gas Recirculation (EGR) on the emissions of Carbon Monoxide (CO) from a turbocharged diesel engine.Tests were carried at different engine speeds, brake power and EGR ratios. The experimental results obtainedshowed that the emissions of carbon monoxide are significantly affected by changes in engine speed, EGR ratio andBrake Power. As a result a simple quantitative correlation which relates CO emissions to engine speed, EGR ratioand brake power is presented. A reasonable agreement was shown when the measured experimental and predictedresults are compared